COMMUNITY METABOLISM OF A CORAL REEF EXPOSED TO NATURALLY VARYING DISSOLVED INORGANIC NUTRIENT LOADS - Silverman Ja.; Lazar B.; Erez J. (My University, 2007)
Daily community rates of calcification, photosynthesis and respiration were measured on a coral reef located in the Northern Red Sea, Gulf of Eilat, Israel between March 2000 and March 2002. This reef is exposed to seasonally varying levels of inorganic nutrient loading due to mixing and stratification of the adjacent open sea water column. Net production measurements were positively and linearly correlated with open sea nutrient levels, and the community photosynthesis to respiration ratio varied between 0.9 and 1.7 accordingly. Community calcification varied between 30 ± 20 and 60 ± 20 mmol C m−2 day−1 during summer and winter, respectively. Under increased nutrient loading the relation between community calcification and aragonite saturation state is suppressed by 30% on average. Both of these findings demonstrate the deleterious effects of nutrient loading on coral reefs.
Keywords: CORAL REEFS; EUTROPHICATION; COMMUNITY METABOLISM; CALCIFICATION; PHOTOSYNTHESIS; RESPIRATION